Cartilaginous melanoma: case report and review of the literature Melanoma cartilagíneo: caso clínico e revisão da literatura - Parente Joana Devesa; José Manuel Pereira da Silva Labareda; Elvira Augusta Felgueira Leonardo Fernandes Bártolo; Maria Fernanda Sachse Pinto Fonseca Santos; Esmeralda Maria Seco do Vale (Sociedade Brasileira de Dermatologia, 2013)
Malignant melanoma can present a variety of histopathological patterns. Cartilaginous change in the absence of osteogenic differentiation is extremely rare in malignant melanoma, being among the least frequent of the wide range of melanoma histologic patterns. We report a case of a 47-year-old woman with a subungual nodule on her right great toe for many years. Histopathological examination of the lesion led to a diagnosis of malignant melanoma with cartilaginous differentiation devoid of concomitant osseous areas. It would appear that this unusual form of melanoma has a predilection for acral location, particularly the subungual region. Malignant melanoma with chondroid stroma should therefore be considered in the differential diagnosis of cartilaginous lesions of the toes and fingers. Careful examination of the overlying epidermis and identification of an in situ component of melanoma may be necessary in order to establish the correct diagnosis. O melanoma maligno pode apresentar uma grande variedade de padrões histopatológicos. A presença de diferenciação cartilagínea, na ausência de diferenciação osteogénica, é extremamente rara no melanoma maligno. O melanoma cartilagíneo está entre os padrões histológicos menos frequentes. Relatamos um caso de uma doente do sexo feminino de 47 anos de idade com um nódulo subungueal no 1º dedo do pé direito com muitos anos de evolução. O exame histopatológico da lesão revelou melanoma cartilagíneo, sem áreas de diferenciação osteogénica. Esta variante de melanoma parece ter predileção pela extremidades, sobretudo pela região subungueal. Assim, o melanoma maligno com diferenciação condróide, deve ser tido em consideração no diagnóstico diferencial de lesões acrais cartilagíneas. A observação cuidadosa da epiderme e a identificação de um componente do melanoma in situ podem ser necessários para estabelecer um diagnóstico correto.